The Myosin Duty Ratio Tunes the Calcium Sensitivity and Cooperative Activation of the Thin Filament - Webb, Milad (Biochemistry, 2013)
In striated muscle, calcium binding to the thin filament (TF) regulatory complex activates actin–myosin ATPase activity, and actin–myosin kinetics in turn regulates TF activation. However, a quantitative description of the effects of actin–myosin kinetics on the calcium sensitivity (pCa(50)) and cooperativity (n(H)) of TF activation is lacking. With the assumption that TF structural transitions and TF–myosin binding transitions are inextricably coupled, we advanced the principles established by Kad et al. [Kad, N., et al. (2005) Proc. Nati. Acad. Sci. U.S.A. 102, 16990–16995] and Sich et al. [Sich, N. M., et al. (2011) J. Biol. Chem. 285, 39150–39159] to develop a simple model of TF regulation, which predicts that pCa(50) varies linearly with duty ratio and that n(H) is maximal near physiological duty ratios. Using in vitro motility to determine the calcium sensitivity of TF sliding velocities, we measured pCa(50) and n(H) at different myosin densities and in the presence of ATPase inhibitors. The observed effects of myosin density and actin—myosin duty ratio on pCa(50) and n(H) are consistent with our model predictions. In striated muscle, pCa(50) must match cytosolic calcium concentrations and a maximal n(H) optimizes calcium responsiveness. Our results indicate that pCa(50) and n(H) can be predictably tuned through TF–myosin ATPase kinetics and that drugs and disease states that alter ATPase kinetics can, through their effects on calcium sensitivity, alter the efficiency of muscle contraction.